The Asymmetric Effect of Exchange Rate on the Household Consumption Expenditures - Raheel Gohar; Bisharat Hussain Chang; Emmanuel Uche; Pervez Ahmed Memon; Kashif Bhatty (Faculty of Economic and Business, 2023)
Previous literature on the exchange rate and household consumption failed to examine the effect of positive and negative changes in the exchange rate on household consumption expenditures. We extended the available literature by investigating the asymmetric impacts in African emerging economies (AEE). To attain this aim, we utilized the nonlinear ARDL model, which covers both negative and positive shocks in the exchange rate. Our results indicate that movements in the exchange rate have asymmetric impacts on household consumption in all the included emerging economies, excluding Nigeria. Our findings propose recommendations for the policymakers to ensure the alignment of the optimal exchange rate for countries of emerging African economies and propose relevant policies for the countries.JEL Classification: D12, D60, I30How to Cite:Gohar, R., Chang, B. H., Uche, E., & Bhatty, K. (2023). The Asymmetric Effect of Exchange Rate on the Household Consumption Expenditures. Etikonomi, 22(1), 31–44. https://doi.org/10.15408/etk.v22i1.23428.